Chiral Polyurea with L-Lysinyl Residue Aimed for Optical Resolution - Hatanaka, Makoto; Nishioka, Yuki; Yoshikawa, Masakazu (Journal of Membrane and Separation Technology, 2013)
Novel polyurea was synthesized from lysinyl residue, L-lysine-4-nitroanilide (L-Lys-4-NA) and 1,4-phenylene diisocyanate (1,4-PDI). The polyurea thus prepared gave durable self-standing membranes. The polyurea was converted into molecular recognition materials by using Z-D-Glu or Z-L-Glu as a print molecule. The Z-D-Glu molecularly imprinted membrane adsorbed the D-isomer of Glu in preference to the corresponding L-isomer and vice versa. Even though the polyurea consisted of L-lysinyl residue, both Z-D-Glu and Z-L-Glu worked as print molecules to construct molecular (chiral) recognition sites in the membrane. Those two types of molecularly imprinted membrane show chiral separation abilities, adopting a concentration gradient or an applied potential difference as a driving force for membrane transport.